Sunday

April 20, 2014

April 20, 2014

Posted by **Lauren** on Saturday, January 7, 2012 at 8:44pm.

a.) ~q -> p

b.) ~q -> ~p

c.) q -> p

d.) q -> ~p

- Geometry -
**bobpursley**, Saturday, January 7, 2012 at 8:51pmI am not certain of your usage of ->, but I have a technique you can use that will work always.

Construct a truth table, such as this:

http://www.gateways2learning.com/SetTheory/EquivalentStatements.pdf

- Geometry -
**Steve**, Sunday, January 8, 2012 at 3:31pmIt is just like your previous post. The contrapositive of

~p -> q

reverses the direction of implication, and the logical values:

~(q) -> ~(~p)

~q -> p

**Related Questions**

math - Question: Use logical equivalnces to show that the propositions !p ->...

Discrete math - Question: Use logical equivalnces to show that the propositions...

Geometry - A conditional statement is always logically equivalent to its a.) ...

Geometry - In logic, which of the following is said to be logically equivalent ...

math - Which statement is logically equivalent to ~a ¨ b? a ¨ ~b b ¨ ~a ~b...

Geometry - Given circle A with circumference 20 pi and the length of arc KD ...

Math-truth table, please check my work! - p -> ~q , p -> q Are these ...

Geometry - Look at the statement below. All dogs are mammals. Which of these ...

Math - I had this equivalent equation question from earlier and I'm not sure if ...

discrete mathematics with applications - Determine which of the following pairs ...